GROWTH AND PRODUCTION OF SWEET CORN PLANTS (Zea mays saccharata. Strut) FROM THE EFFECT OF FERMENTATION OF SEVERAL MIXTURES OF PALM OIL MILL SOLID WASTE (LPKS) WITH COW SOLID (LTS) - Meriksa Sembiring; Risdawati Ginting (Bajang Institute, 2023)
The research was carried out in Sei Mecirim Village Market 4 Sunggal District with an altitude of + 400 meters above sea level, Andosol soil type, the research will be carried out from July to September 2023. With the research title